2003
DOI: 10.1016/s0379-0738(03)00350-5
|View full text |Cite
|
Sign up to set email alerts
|

Homicide–suicide in Hong Kong, 1989–1998

Abstract: This study provides the first systematic research of homicide-suicide (HS) in a Chinese society. Data were drawn from the HK Homicide Monitoring Data-base computer file derived from investigation and death reports held by the HK Police Force and the Coroner's Court. During the 10-year study period, 56 events involving 133 deaths were identified. The majority of offenders were males (75%) and most victims were female (64%). The mean age of offenders and victims were 41.9 and 32.3 years, respectively. Spouses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 23 publications
8
74
1
3
Order By: Relevance
“…1,2,6 As opposed to the other western countries, the present study shows family dispute to be the prime motive for murder-suicide. Family disputes involve multiple inter-related problems.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…1,2,6 As opposed to the other western countries, the present study shows family dispute to be the prime motive for murder-suicide. Family disputes involve multiple inter-related problems.…”
Section: Discussioncontrasting
confidence: 74%
“…During their study Milroy, 1,13 Chan et al, 2 Cohen et al, 3 Carcach et al, 4 Saleva et al, 6 Campanelli and Gilson, 8 Hannah et al, 9 Lecomte and Fornes, 10 Barraclough and Harris, 11 Stack, 12 Hanzlick and Koponen, 15 Marzuk et al 16 and Gowitt and Hanzlick, 20 observed that males were the most common offenders in the murder-suicide cases. Milroy 1 reported the father to be the common perpetrator.…”
Section: Discussionmentioning
confidence: 97%
“…They report a rate of 0.2-0.3 per 100,000 persons in the United States. Several researchers have found similar rates in the United States (2,(4)(5)(6) and outside the United States (7). Malphurs and Cohen (8) searched the prevalence of homicide-suicide in the United States using newspaper surveillance over a three-year period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The vast majority of homicide-suicide perpetrators are males (1,(4)(5)(6)(7)(8)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Of all the studies reviewed, West (20) found the lowest percentage of male perpetrators at 59.5% of perpetrators.…”
Section: Sex and Agementioning
confidence: 99%
“…A study in Hong Kong found that roughly one out of three violent offenders were under financial pressure when committing homicide, and more than one out of four offenders appeared directly motivated by economic distress. 18 Economic stress is also a major source of family tension and a leading cause of family breakup. 17 A survey of 630 domestic violence shelters in the USA reported a 75% increase in the number of requests for services since the onset of the crisis.…”
Section: Introductionmentioning
confidence: 99%